Meningkatkan Kemampuan Membaca Anak Melalui Permainan Memancing Huruf Di Kelompok B TK Siti Khotijah Jatiurip Krejengan Probolinggo - Deppy, Deppy; Asia, Nur (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2022)
Abstract The reading ability of children in Group B of Siti Khotijah Jatiurip Krejengan Probolinggo Kindergarten is still lacking. The concept of learning with games for children is still not optimal. Some children's ability to recognize letters and words is still lacking. Some children can only say the letters but don't know the shape of the letters. The aim of this classroom action research is to improve the reading and letter recognition skills of students in group B Kindergarten, Jatiurip, Krejengan, totaling 13 children, Probolinggo . The type of research used is Classroom Action Research. Based on the results of the actions that have been taken, it can be concluded that through the fishing game the letters of the alphabet increase the reading ability of children in Group B Kindergarten Siti Khotijah Jatiurip Krejengan Probolinggo. Keywords: Reading; Child; Fishing Letters.